Analysis of cardiac autonomic modulation in obese and eutrophic children - Marques Vanderlei, Luiz Carlos [UNESP] (2010)
INTRODUCTION: Obesity causes alterations in cardiac autonomic function. However, there are scarce and conflicting data on this function with regard to heart rate variability in obese children.OBJECTIVE: To compare the autonomic function of obese and eutrophic children by analyzing heart rate variability.METHODS: One hundred twenty-one children (57 male and 64 female) aged 8 to 12 years were distributed into two groups based on nutritional status [obese (n = 56) and eutrophic (ideal weight range; n = 65) according to the body mass index reference for gender and age]. For the analysis of heart rate variability, heart rates were recorded beat by beat as the children rested in the dorsal (prone) position for 20 minutes. Heart rate variability analysis was carried out using linear approaches in the domains of frequency and time. Either Student's t-test or the Mann-Whitney U-test was applied to compare variables between groups. Statistical significance was set at 5%.RESULTS: The SDNN, RMSSD, pNN50, SD1, SD2, LF and HF indices in milliseconds squared were lower among the obese children when compared to the eutrophic group. There were no alterations in the SD1/SD2 ratio, LF/HF ratio, LF index or HF index in normalized units. There was a significant difference between groups in the RR interval (R-to-R EKG interval).CONCLUSION: The obese children exhibited modifications in heart rate variability, characterized by a reduction in both sympathetic and parasympathetic activity. These findings stress the need for the early holistic care of obese children to avoid future complications.